2013
DOI: 10.1016/j.jecp.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Children and adults use attractiveness as a social cue in real people and avatars

Abstract: Observing social interactions between children and adults is a major method in the toolkit of psychologists who examine social development and social relationships. Although this method has revealed many interesting phenomena, it cannot determine the effect of behavior independent of other traits. Research on the role of attractiveness in social development provides an example of this conundrum: Are attractive and unattractive children/adults treated differently because of their attractiveness (independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…For instance, participants experience greater learning gains after interacting with computer-controlled tutors depicted as ''experts'' when the character's race is nontraditional (i.e., African-American versus Caucasian), as perhaps this is unexpected and, thus, makes participants pay more attention (Baylor & Kim, 2004). In addition, adults and children prefer physically attractive avatars as partners (Principe & Langlois, 2013), and attractive avatars are more persuasive (Holzwarth, Janiszewski, & Neumann, 2006). In general, realistic virtual characters influence social behavior more reliably than less realistic characters (Guadagno et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, participants experience greater learning gains after interacting with computer-controlled tutors depicted as ''experts'' when the character's race is nontraditional (i.e., African-American versus Caucasian), as perhaps this is unexpected and, thus, makes participants pay more attention (Baylor & Kim, 2004). In addition, adults and children prefer physically attractive avatars as partners (Principe & Langlois, 2013), and attractive avatars are more persuasive (Holzwarth, Janiszewski, & Neumann, 2006). In general, realistic virtual characters influence social behavior more reliably than less realistic characters (Guadagno et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Khan and De Angeli (2009) similarly found that avatars that were rated as more attractive were also perceived as more intellectually-, socially-and morally-competent. They were also preferred as social partners (Principe & Langlois, 2013). Additionally, Yee et al (2009) found that when users were assigned to taller avatars, they behaved more aggressively in a negotiation task.…”
Section: Second Life (Sl) and Avatarsmentioning
confidence: 98%
“…In addition to the potential for continuity between users and their online avatars, the standards and stereotypes embedded in larger sociopolitical contexts can also seep into online contexts (Boellstorff, 2008;Kendall, 1998;Lehdonvirta, Nagashima, Lehdonvirta, & Baba, 2012;Palomares & Lee, 2010;. Past studies suggest that, much like offline appearance, avatar appearance matters when it comes to creating positive interactions online for youth and adults (Dehn & Van Mulken, 2000;Messinger et al, 2008;Nowak & Rauh, 2005;Principe & Langlois, 2013;Yee, Bailenson, & Ducheneaut, 2009). For example, Messinger et al (2008) found that people who created SL avatars that were more attractive than their offline selves reported being more outgoing, extraverted, risk-taking, and loud online.…”
Section: Second Life (Sl) and Avatarsmentioning
confidence: 99%
See 2 more Smart Citations